ANALISIS SITEM PELAYANAN ANTRIAN PADA BANK BNI SYARIAH CABANG KOTA PALU - Ilham, Ilham (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
This study aims to determine the performance of tellers 1 and 2 in serving deposit and withdrawal transactions. The problem (1). Identify the queuing service characteristics applied by Bank BNI Syariah Palu Branch (2). Seeing the performance of the busiest teller services 1 and 2. The busiest service performance results (?) are found in teller 2, which is 0.3687 or 36.87%, for teller 1 is 0.3393 or 33.93%, while for the next calculation has a value of 1 customer probability 1 teller in the system (P0) 0.6605, teller 2 is 0.6311, the average number of customers in the system (Ls) for teller 1 is 0.5208 while for teller 2 is 0.5852, for average time in the system (Ws) for tellers 1 ie 0.1025 is equal to teller 2 which is 0.1025, then the average number of customers in the queue (Lq) for teller 1 is 0.1814 while for teller 2 is 0.2164 and the last is the average time in the queue (Wq) for teller 1 which is 0.0362 equal to teller 2 which is 0.04. So the conclusion is that the service performance for these two telephones has the same level of value.